Primary resistance to integrase strand transfer inhibitors in Spain using ultrasensitive HIV-1 genotyping. (15th September 2020) - Casadellà, M; Santos, J R; Noguera-Julian, M; Micán-Rivera, R; Domingo, P; Antela, A; Portilla, J; Sanz, J; Montero-Alonso, M; Navarro, J; Masiá, M; Valcarce-Pardeiro, N; et al.
Abstract: Background: Transmission of resistance mutations to integrase strand transfer inhibitors (INSTIs) in HIV-infected patients may compromise the efficacy of first-line antiretroviral regimens currently recommended worldwide. Continued surveillance of transmitted drug resistance (TDR) is thus warranted. Objectives: We evaluated the rates and effects on virological outcomes of TDR in a 96 week prospective multicentre cohort study of ART-naive HIV-1-infected subjects initiating INSTI-based ART in Spain between April 2015 and December 2016. Methods: Pre-ART plasma samples were genotyped for integrase, protease and reverse transcriptase resistance using Sanger population sequencing or MiSeq™ using a ≥ 20% mutant sensitivity cut-off. Those present at 1%–19% of the virus population were considered to be low-frequency variants. Results: From a total of 214 available samples, 173 (80.8%), 210 (98.1%) and 214 (100.0%) were successfully amplified for integrase, reverse transcriptase and protease genes, respectively. Using a Sanger-like cut-off, the overall prevalence of any TDR, INSTI-, NRTI-, NNRTI- and protease inhibitor (PI)-associated mutations was 13.1%, 1.7%, 3.8%, 7.1% and 0.9%, respectively. Only three (1.7%) subjects had INSTI TDR (R263K, E138K and G163R), while minority variants with integrase TDR were detected in 9.6% of subjects. There were no virological failures during 96 weeks of follow-up in subjects harbouring TDR as majority variants. Conclusions: Transmitted INSTI resistance remains rare in Spain and, to date, is not associated with virological failure to first-line INSTI-based regimens.